Análise do transcriptoma da interação Xanthomonas fuscans subsp. aurantifolii tipo C e plantas cítricas - Silva, Claudênia Ferreira da [UNESP] (2015)
The bacterium Xanthomonas fuscans subsp. aurantifolii type C (XAC) is the causative agent of cancrose C, which affects only acid lime 'Galego' (Citrus aurantifolia (Christm) Swingle). The main phenotypic characteristic of this disease is the hyperplasia and hypertrophy of the affected tissue, leading to the formation of erupescentes characteristic lesions, and responsible for the abnormal cell growth is a transcription activator-like (TAL) effector family (also called the avrBs3/pthA family), which is injected into the plant by the type type III secretion system (T3SS) and is translocated to the nucleus, where it interacts with UPA-box regions (up-regulated by AvrBs3) and acts as a transcriptional activator. The sweet orange varieties are resistant, and when inoculated with XauC show strong hypersensitive response (HR), causing local programmed cell death (apoptosis) and abscission of affected leaves. The mechanisms that give the acid lime 'Galego' susceptibility to XauC is not known. This study aimed to identify, through next-generation sequencing (NGS), plant differentially expressed transcripts involved in host-pathogen interaction in pathosystems XauC-orange 'Hamlin' (species resistant) and XauC-acid lime 'Galego' (species susceptible). Leaves from 'Hamlin' and acid lime 'Galego' were inoculated with XauC suspension at a concentration of 106 cfu/mL (experimental) or sterile water (control) and collected at 5 and 7 days after inoculation (dai). Total RNA was extracted and used for transcriptome analysis by RNA-seq. The transcripts obtained from sequencing were normalized and redundancies removed. A single bank of genomic data and citrus transcripts was assembled, which was called CitSeqDB and is the junction of 6 public banks: AFFYM, NCBI Unigene, USDA, CITRUSGDB and PHYTOZOME. Transcripts that proved to be differentially expressed relative to controls were confronted with the bank and functional annotation was performed using ...